If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + 1) = 3x + 8 Reorder the terms: -2(1 + x) = 3x + 8 (1 * -2 + x * -2) = 3x + 8 (-2 + -2x) = 3x + 8 Reorder the terms: -2 + -2x = 8 + 3x Solving -2 + -2x = 8 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -2 + -2x + -3x = 8 + 3x + -3x Combine like terms: -2x + -3x = -5x -2 + -5x = 8 + 3x + -3x Combine like terms: 3x + -3x = 0 -2 + -5x = 8 + 0 -2 + -5x = 8 Add '2' to each side of the equation. -2 + 2 + -5x = 8 + 2 Combine like terms: -2 + 2 = 0 0 + -5x = 8 + 2 -5x = 8 + 2 Combine like terms: 8 + 2 = 10 -5x = 10 Divide each side by '-5'. x = -2 Simplifying x = -2
| y=8-3(2+3) | | 3 = c4– 1 | | 3y+12=-57 | | 3x+4yx=16 | | 6x+800=10x+1000 | | 1/2x(2x-18)=4x | | 4x+2x-15+x=4x-3 | | Sin^4(x)-1=0 | | 15x-3=-4x+55 | | 2x-3(4x+7)=3x+5 | | 8xb-3=19 | | -135=-5(-5-8n) | | 2x-1+6x-8=180 | | 455=7(1-8a) | | 8(6n+2)-8=104 | | 3x-9=13x-59 | | 9=-1/15x | | 0.5e+20=25 | | -7(6+n)=-91 | | Y=3c+11 | | -4(2n+8)-5n=-97 | | -27+8=-12+x+20 | | 15-3b=63 | | -91=-7(b+7) | | 7x2/2 | | 301=-7(6x-7) | | -152=8(-2k-3) | | 5(x-5)+2(-4x+8)=-3x+13 | | -3q^2+14q+49=0 | | 9x^3y^8z^17/-3x^5y^5z^10 | | -4(4x+1)=-116 | | -4x+3x-4=0 |